Childfree, millennial marriage disorientation, and Islamic family law perspectives - Syarafuddin, Muhsan; Fauzi, Ahmad (Communications in Humanities and Social Sciences, 2023)
Childfree refers to the conscious decision of an individual or couple to abstain from parenthood, independent of biological or adoptive possibilities as a lifestyle choice unrelated to fertility. This study investigated childfree contents on social media, specifically in Instagram, among millennials. Additionally, it delved into Islamic family law perspectives on childfree living. Utilizing qualitative content analysis, the chosen Instagram account for examination was Childfree Life Indonesia @childfreelife.id. The research identified some reasons for embracing childfree living, including past trauma, personal autonomy, happiness pursuit, career focus, financial considerations, and environmental preferences. Benefits encompass career advancement, reduced responsibilities, financial stability, improved mental health, emotional fulfillment, personal time, flexibility, and expanded leisure. Conversely, drawbacks involve the potential lack of support in old age, loneliness, absence of family legacy, no parenting experience, no successors, societal judgment, limited social network, a sense of family incompleteness, and diminished social support. Islamic family law emphasizes the marriage goal of progeny for societal strength, deeming permanent and unjustified childfree choices as prohibited (haram). However, temporary and justified childfree decisions may align with Islamic principles. This study contributes scholarly insights into millennial marriage dynamics, incorporating media and Islamic family law perspectives, with practical implications for fostering a nuanced understanding of Islamic teachings and societal trends among millennials, averting behaviors incongruent with religious norms.